Humanities in the education of engineers at community Universities in Rio Grande do Sul: The usefulness of the "useless" (Revista Contexto & Educação, 2025)
This article results from theoretical and documentary research, with a qualitative approach, to understand the trend(s) guiding the inclusion/approach and/or exclusion of humanities in academic education in Engineering courses at the 14 community universities in Rio Grande do Sul, aiming to develop a critique that can creatively support a counter-discourse to the instrumental paradigm in Higher Education. Data collection involved accessing the universities' public web pages to identify the profile of graduates and the content/disciplines related to humanities education and in the National Curriculum Guidelines (DCNs) for Engineering. Data analysis was conducted through content analysis. Findings point to a critical situation in these courses regarding humanistic education, considering the low percentage of these disciplines and contents offered in the curricula. There are inconsistencies between the profiles of graduates and the curriculum design, revealing the effects of instrumental rationality and the blindness of reductionist knowledge, which impacts the loss of self and human subjectivity. There is an urgent need for a counterpoint in the education of university students by finding mechanisms to make it a "studious space" that prioritizes holistic education, transcending instrumental logic.
Keywords: Higher education; Instrumental rationality; Humanities